2005
DOI: 10.1111/j.1365-3040.2005.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and carbohydrate metabolism in tobacco leaves during an incompatible interaction with Phytophthora nicotianae

Abstract: The metabolic and cellular changes in source leaves of Nicotiana tabacum L. cv SNN during an incompatible interaction with Phytophthora nicotianae van Breda de Haan were investigated and compared with defence reactions. Hypersensitive cell death was preceded by a rapid and highly localized shift to non-assimilatoric metabolism. During the first 6 h post infection (hpi), reactive oxygen species (ROS) accumulated. Callose was deposited at the interface of adjacent mesophyll cells ( ≥ 1 hpi), the export of sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
196
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(220 citation statements)
references
References 61 publications
20
196
1
3
Order By: Relevance
“…S3). In summary, these changes effectively alter carbon partitioning in favor of metabolic sourceto-sink transitions within infected leaf areas (5,6). Additional evidence for an altered pathogen response in cP2 plants is the accumulation of transcripts encoding PR-Q (5), which now also occurred in the Xanthi background, comparable with the resistant SNN (Fig.…”
Section: Expression Of a Plastidic G6pd Isoform In The Cytosol Of A Smentioning
confidence: 85%
See 2 more Smart Citations
“…S3). In summary, these changes effectively alter carbon partitioning in favor of metabolic sourceto-sink transitions within infected leaf areas (5,6). Additional evidence for an altered pathogen response in cP2 plants is the accumulation of transcripts encoding PR-Q (5), which now also occurred in the Xanthi background, comparable with the resistant SNN (Fig.…”
Section: Expression Of a Plastidic G6pd Isoform In The Cytosol Of A Smentioning
confidence: 85%
“…Immunoblot analyses with various G6PDH antisera (14,19) demonstrated that these defense-induced rises in G6PDH activity mainly result from up-regulated expression of cytosolic isoforms, encoded by G6PD (Fig. 1B), probably due to sensing elevated soluble sugar levels (7), known to accompany sourceto-sink transitions of infected tobacco source leaves (5,6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, overexpression of CWIN in rice (Oryza sativa) driven by its native promoter enhanced grain filling and yield (Wang et al, 2008). An increase in CWIN transcription or activity is also commonly observed upon pathogen infection in a wide range of plant species (Benhamou et al, 1991;Scharte et al, 2005), indicating a role for CWIN in defense against pathogens, possibly through Glc signaling (Ruan, 2014). For instance, constitutive expression of a yeast (Saccharomyces cerevisiae) INV gene in the apoplasm increased tobacco (Nicotiana tabacum) resistance to potato virus Y (Herbers et al, 1996), whereas RNA interference (RNAi)-mediated repression of CWIN in tobacco compromised its response to infection by the oomycete Phytophthora nicotianae (Essmann et al, 2008).…”
mentioning
confidence: 99%
“…Preliminary experiments on the mechanism of photosynthesis inhibition as measured by P700 redox kinetics [23] indicate that the electron transport chain might be restricted upstream of photosystem I (PS I, data not shown). The effect of nostocarboline might be comparable to the non-selective herbicide paraquat (methylviologen, 1,1'-dimethyl-4,4'-bipyridinium), which is a strong autooxidable electron acceptor in PS I; and its presence in light-exposed plants has several drastic consequences, like the production of superoxide.…”
Section: Resultsmentioning
confidence: 99%